Open Access to Research Data: Strategic Delay and the Ambiguous Welfare Effects of Mandatory Data Disclosure - Frank Mueller-Langer; Patrick Andreoli-Versbach (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2014)
Mandatory data disclosure is an essential feature for credible empirical work but comes at a cost: First, authors might invest less in data generation if they are not the full residual claimants of their data after their first publication. Second, authors might strategically delay the time of submission of papers in order to fully exploit their data in subsequent research. We analyze a three-stage model of publication and data disclosure. We derive exact conditions for positive welfare effects of mandatory data disclosure. However, we find that the transition to mandatory data disclosure has negative welfare properties if authors delay strategically.
Keywords: B40; C80; L59; 330; data disclosure policy; strategic delay; welfare effects